Modification in the microstructure of sodium carboxymethylcellulose/polyvinyl alcohol polyblend films through the incorporation of NaNO3 for energy storage applications. (29th August 2022) - Cyriac, Vipin; Ismayil,; Noor, Ikhwan Syafiq Bin Mohd; Rojudi, Z. E.; Sudhakar, Y. N.; Chavan, Chetan; Bhajantri, Rajashekhar F.; Murari, M. S.
Summary: In this work, the effect of NaNO3 salt concentration (0, 5, 10, 15, 20, 25, and 30 wt.%) on the structural, electrical, and mechanical properties of Na‐carboxymethyl cellulose/polyvinyl alcohol polyblend electrolyte films has been studied. X‐ray diffraction showed an increase in the amorphous phase of the polymer blend with increasing salt concentration up to samples containing 20 wt.% of NaNO3 supported by the scanning electron microscope studies. Fourier‐transform infrared analysis confirmed the complexation of the salt via coordinate bond/hydrogen bond with –OH and –CH groups of the polymer blend. The T g of the samples have been found to increase with salt concentration indicating transient cross‐links. Nyquist plot fitting has been performed to evaluate the transport properties; hence carrier concentration influences ionic conductivity. The sample complexed with 20 wt.% of NaNO3 revealed the highest room temperature conductivity of 1.75 × 10 −4 S cm −1, among all other samples with suitable mechanical strength to be incorporated into energy storage devices. The highest conducting electrolyte has been incorporated into a primary battery to showcase its potential application in energy storage devices. Abstract : Schematic representation of the preparation of polyblend electrolyte films (created using biorender.com).